Analysis of the Level of Interest of the Cipocok Jaya Community in Volleyball: A Survey-Based Descriptive Study - Iskandar, Asah; Qohhar, Wildan; Dwi Ariani, Egiesta (Mamaos:Journal Physical Education, Sport and Art, 2025)
Public interest in sports plays a crucial role in improving health, fitness, and active participation in physical activities. Observations in Puri Anggrek indicate that although volleyball is quite popular, community involvement is not yet optimal. This study aims to analyze the level of interest in volleyball among the Puri Anggrek community based on intrinsic and extrinsic factors. The research method used a descriptive approach with 66 respondents aged 20–40 years selected through purposive sampling. Data collection was conducted using a closed-ended questionnaire containing 33 statements that had been tested for validity and reliability. Data analysis used descriptive statistics in the form of mean, median, standard deviation, and interest categorization based on standard deviation intervals. The results showed that overall community interest was in the moderate category. Intrinsic factors, including enjoyment, attention, and activity, were also in the moderate category, as were extrinsic factors, including environmental and family support. These findings illustrate that community interest has been established, but still requires strengthening through increasing positive experiences, access to activities, and consistent environmental support.